Effects of rosehip sauce on chemical, oxidative and sensorial quality of marinated anchovy (Engraulis Encrasicolus Linnaeus, 1758) - Kaya, Gulderen Kurt; Coban, Ozlem Emir; Bilici, Resit (Codon Publications, 2023)
Marinated anchovies are of economic importance in Turkey. However, natural antioxidants affecting quality of marinated anchovies are rarely addressed. The purpose of this study is to compare olive oil and rosehip sauce as fillers in anchovy marinades. The study investigated the effects of rosehip sauce on the quality of marinated anchovies stored at 4 degrees C. Anchovy were marinated with 4% acetic acid and 12% NaCl, put into plastic jars, filled with either olive oil or rosehip sauce and stored at 4 degrees C. Changes in sensory attributes were determined during the process, and the following chemical parameters were monitored: total phenolic content (mg/100 g GAE), total volatile basic nitrogen (mg/100 g), pH, peroxide value (meq/kg) and thiobarbituric acid (mg MDA/kg). Values of total volatile basic nitrogen (TVB-N), peroxide value (PV) and thiobarbituric acid (TBA) increased during the storage. Higher values of TVB-N, TBA and PV were found in samples with olive oil than those with rosehip sauce. Samples with rosehip sauce demonstrated better oxidative stability. Rosehip sauce samples had higher appearance, odor, color and texture scores than olive oil samples.
Keywords: fish marinades; marinated anchovy; olive oil; quality changes; rosehip sauce; sauces